ANÁLISE DE LACUNARIDADE DE DISTRIBUIÇÃO ESPACIAL DE QUEIMADAS NA AMAZÔNIA LEGAL - LUCENA, Leandro Ricardo Rodrigues de; SANTOS, Carlos Renato dos; STOSIC, Tatijana; CUNHA FILHO, Moacyr (Brazilian Journal of Biometrics, 2017)
In this work we analyze spatial variability of forest fires detected in the Legal Amazon region during the period 2000-2013, using the lacunarity method. The results show that for years with higher number of forest fires, the values of lacunarity were lower (indicating more homogeneous behavior), while for years with lower number of forest fires, the values of lacunarity were higher (indicating more heterogeneous behavior). The different properties of spatial distribution of forest fires are also observed for rainy and dry season.